TRANSFORMING BUSINESS MODELS: INNOVATIONS FROM AGRICULTURE TO AQUACULTURE - Jia-Ru Lin; Te-Tsai Lu (International Journal of Application on Economics and Business, 2026)
Taiwanese agriculture has long been under pressure from climate change, labor shortages, and volatile market prices. Smallholders often remain in a weak bargaining position due to limited scale, making it difficult to stabilize output and accumulate added value. Using a qualitative case study approach, the present study examines the transformation of a greenhouse muskmelon farm from 2019 to 2025 and synthesizes a six-stage innovative operating model consisting of (1) technological adoption, (2) grading and packaging, (3) channel development, (4) supply-demand planning, (5) team organization and division of labor, and (6) brand building. The findings show that facility-based cultivation and precision management reduce climate risks and improve product consistency; standardized grading and packaging enhance product identification and market trust; and access to wholesale channels and market intelligence enables the case to shift from a price taker to a supply-chain coordinator. Team-based aggregation and staggered production increase shipment volumes and bargaining power, while branding and traceability help the product enter mid-to-high-end markets and capture price premiums. The proposed model is further transferred to and validated in a hard clam aquaculture case. Results indicate that smart water-quality monitoring, standardized grading and packaging, diversified channels, and staged harvesting improve survival rates, stabilize cash flow, and strengthen brand trust. Overall, the six-stage model demonstrates cross-industry transferability and provides a practical reference for enhancing resilience and sustainable competitiveness among small-scale farmers and aquaculture operators in Taiwan.